2001
DOI: 10.1038/sj.leu.2402026
|View full text |Cite
|
Sign up to set email alerts
|

ABL1 methylation in Ph-positive ALL is exclusively associated with the P210 form of BCR-ABL

Abstract: In human Ph-positive leukemia there is a clear association of different forms of the BCR-ABL oncogene with distinct types of leukemia. The P190 form of BCR-ABL is rarely observed in chronic myeloid leukemia (CML) but is present in 50% of Phpositive acute lymphoblastic leukemia (ALL). In contrast, the P210 form is observed both in CML and 50% of Ph-positive ALL. Methylation of the proximal promoter of the ABL1 gene has been shown to be a nearly universal event associated with clinical progression of CML. This r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…The bisulfite reagent was prepared as follows: 1.9 g of sodium bisulfite (Sigma Israel, Rehovot) were slowly dissolved in sterile water on a gentle rocker. The total volume was 4 ml, containing 0.7 ml 2 N NaOH and 0.5 ml of a saturated solution of hydroquinone (Sigma) in water (Shteper et al, 2001).…”
Section: Cellsmentioning
confidence: 99%
“…The bisulfite reagent was prepared as follows: 1.9 g of sodium bisulfite (Sigma Israel, Rehovot) were slowly dissolved in sterile water on a gentle rocker. The total volume was 4 ml, containing 0.7 ml 2 N NaOH and 0.5 ml of a saturated solution of hydroquinone (Sigma) in water (Shteper et al, 2001).…”
Section: Cellsmentioning
confidence: 99%
“…Expression of CD10 was inversely associated with methylation of CD10. At the genetic level, methylation of c-ABL was only observed in patients with Philadelphia chromosome alterations (Ph), and only in those patients with the p210 isoform, a reproducible result 31 . In the exploratory study, an association was observed between methylation and worse prognosis (for p73 and p15).…”
Section: Aberrant Dna Methylation In Allmentioning
confidence: 99%
“…[3,4] Among adult patients with Ph þ ALL, both p190 and p210 are found with equal frequency of 50%; while p190 protein has been described in 90% of pediatric Ph þ ALL. [2,[5][6][7] However, there are no significant hematological or prognostic differences between p210 and p190 expressing Ph þ ALL. [6,7] Pediatric Ph þ ALL usually presents during later childhood with high leukocyte counts and frequent central nervous system involvement.…”
mentioning
confidence: 99%
“…[2,[5][6][7] However, there are no significant hematological or prognostic differences between p210 and p190 expressing Ph þ ALL. [6,7] Pediatric Ph þ ALL usually presents during later childhood with high leukocyte counts and frequent central nervous system involvement. [2,8] Though it is difficult to delineate between de novo BCR-ABL1 positive ALL and blast crisis of chronic myelogenous leukemia (CML), age at diagnosis, absence of splenomegaly and basophilia favor de novo BCR-ABL1 positive ALL.…”
mentioning
confidence: 99%